Deterioration and conservation of rock-hewn sandstone cave-temples in Longdong area, China - Wang, Y (2021)
Cave-temples are multivalent types of immovable cultural heritage which link spiritual values as places for Buddhism rituals, aesthetic values because of the Buddha sculptures, inscriptions and murals they contain, historic values as significant objective evidence of the history of the eastward spread of Buddhism, as well as economic values as tourist attractions. It is, therefore, highly necessary to preserve them in a sustainable manner and pass them on to the next generation. The Longdong area refers to the area to the east of the Long mountains, i.e. the southern section of the Liupanshan mountain chain, in Gansu Province, China. This region was also the eastern section of the Silk Road connecting the Central Plain in China to western countries. A great number of cave-temples are hewn from outcrops of the widespread sedimentary sandstone units in the region and face severe deterioration problems endangering their values and integrity. Thus, study regarding deterioration process is required in order to understand the impacts of these deterioration risks. Accordingly, the research presented in this thesis focuses on studying and evaluating the rock deterioration and its impacts aiming to clarify the major weathering mechanisms of these cave-temples. The North Grotto Temple (NGT), situated near Qingyang, is the oldest site representing the highest artistic value of grotto art in the Longdong area, hence, was selected as the study site. The overall research comprised three phases. The first phase involved field investigation and survey of weathering features; the second phase focused on in situ detection, modelling prediction and laboratory characterization of deteriorating salts, and the third phase comprised laboratory simulation of salt weathering at North Grotto Temple and how it affects the rock properties. A range of portable non-destructive devices (including Karsten tube and surface hardness tester (Proceq Equotip® 3 and 550), ultrasonic instrument (Proceq PunditLab) were used in the research, along with a non-invasive method of sampling salts (fiber paper pulp poultices), a range of laboratory analysis and experimental methods (including ion chromatography and environment cabinet) and modelling software (thermodynamic model - ECOS-RUNSALT). According to the research, several deterioration patterns, such as granular disintegration, efflorescence, alveolar, were identified on the NGT sandstone façade, which illustrate that salt weathering is probably the leading weathering agent at the site. A mixture of salts was predicted to form in the site, i.e. aphthitalite, bloedite, picromerite, darapskite, mirabilite, hexahydrite, starkeyite, nitromagnesite, halite, niter, and sylvite. Large diurnal variation of humidity in the site enhances the likelihood of salt weathering. Laboratory simulation showed experimentally that the salt mixtures can cause material loss, appearance changes and modify the petrophysical properties of sandstones, which badly affects the integrity of rock. In sum, this study illustrates that the sandstone cave-temples in the Longdong area are under cumulative damage from salt weathering. Environmental control is a necessary measure in order to manage the risks threatening the on-going preservation of the sandstone cave-temples.